Implementation of intersubjective samples in musical art lessons: (on the example of a combined lesson in 6th grade on theplanned topic «Rondo») - Kim, Oleksandr (Professional Art Education, 2023)
The article highlights the essence of integrative processes in a modern secondary school, examines the research of domestic and foreign specialists in the field of interdisciplinary connections in music art lessons.Methods and methodology. Traditional pedagogical methods were used in the research, including analytical, comparative, retrospective, logical-systemic, chronological-structural and comparative analysis of scientific-pedagogical and art literature, educational materials, works and contributions of outstanding scholars. At the same time, the research is based on a combination of different methodological approaches, including system-activity, phenomenological, terminological and cognitive.The scientific novelty of the article lies in the generalization of essential categories of integrative and interdisciplinary processes in the conditions of a modern comprehensive school (on the example of a combined lesson in the 6th grade on the planned topic "Rondo").Results. The list of the main directions of implementation of means of integration in the Ukrainian secondary school and in the countries of the East has been revealed. It has been established that the issue of integration with the wide involvement of materials of humanitarian cycle subjects is the object of attention of pedagogues-scientists of Ukraine and the world. Different forms, methods and levels integration of the inter-subject connections are considered on the example of a combined lesson on the planned topic "Rondo" of the program on the subject "Musical Art" for the 6th grade of a comprehensive educational institution (connections between the subjects: music, literature, history, cinematography, theater, physics). During the lesson, fragments of the films "Amadeus", "Mozart and Salieri" (three screen adaptations from different years), "The Marriage of Figaro" were shown in the form of a presentation. Facts from the biography of Mozart, Salieri, Beaumarchais, Benjamin Franklin are given; information about the events of the war for the independence of the United States of America, the activities of Beaumarchais as an inventor and entrepreneur, the activities of Franklin as a politician, diplomat, businessman, oceanographer and physicist. The lesson was conducted in the form of a role-playing "court game", where the roles of the accuser, the defender, and the witness were distributed among the students. The planned result of the lesson, in addition to the coverage of the planned topic, involves the creation of a complete picture of phenomena in the world at the turn of the XVIII-XIX centuries. The issue of formalizing the cooperation of teachers of various disciplines and specialists of higher educational institutions for the improvement of integration processes in general educational institutions at the level of creative groups or even methodical associations is highlighted.Conclusions. The main studies and publications on the problem of interdisciplinary integration in secondary schools are analyzed. The essence of basic categories regarding integrative processes in the conditions of a modern comprehensive school is revealed. The need for cooperation of teachers from various subjects and educational cycles to create a holistic understanding of civilizational values in the modern world in students is substantiated. It has been proven that the reflection of many events and phenomena of nature and society by means of musical art effectively contributes to the achievement of the goals of education and upbringing formulated in the Concept of the New Ukrainian School.
Keywords: Lacrimosa; Serenade; Requiem; Mozart; Beaumarchais; genius; crime; interdisciplinary samples; musical art